Hello!
√7 - y = 6 <=>
<=> -y = 6 - √7 <=>
<=> y = -6 + √7 => √7 - (-6 + √7) = 6
Good luck! :)
Answer:
D is the correct answer.
Step-by-step explanation:
Distribute (−6x^4 + x^2 − 1)(2x^3 - 4x + 3)
-12x^7 + 24x^5 - 18x^4 + 2x^5 - 4x^3 + 3x^2 - 2x^3 + 4x - 3
Combine Like Terms
-12x^7 + 26x^5 - 18x^4 - 6x^3 + 3x^2 + 4x - 3
You use y=mx+b and you get y=6x-33
The figure that shows equivalent ratios for the ratio of sugar to flour would be Figure 2.
<h3>What figure has equivalent ratios?</h3><h3 />
The ratio os sugar to flour is 1:3. An equivalent ratio would be one that is 1:3 or 3:1.
Figure 2's ratios are:
6 :2
9:3
12:4
When all of these are taken to their simplest form, we get:
3 : 1
Figure 2 is therefore an equivalent ratio.
Rest of the question is:
he ratio of sugar to flour used in a pudding recipe is 1:3. Which figure shows equivalent ratios? #1: 3,1. 9,2. 3,15 #2: 6,2. 9,3. 12,4 #3: 9,5. 6,3. 13,1 #4: 9,4. 6,3. 3,2
Find out more on equivalent ratios at brainly.com/question/2328454
#SPJ1
Hello,
Equation of the line: y-4=3(x+1)==>y=3x+7
3 others points: (0,7), (-7/3,0),(1,10) for example.